Determinants of Transition From Child and Adolescent to Adult Mental Health Services: A Western Australian Pilot Study. (16th June 2016) - Perera, Rebecca H; Rogers, Shane L; Edwards, Stephen; Hudman, Paul; Malone, Catherine
Abstract : Objective: The aim of this research was to explore the transition pathways of transition‐aged youth out of child and adolescent mental health services in Perth, Western Australia. A secondary aim was to identify factors that have some impact upon the transition process. Method: Cases discharged from seven child and adolescent mental health community clinics in the Perth metropolitan area, from 1 June 2004 to 30 June 2013, at transition age (16–25 years of age), were examined retrospectively. Two hundred and forty‐five cases met the selection criteria and were reviewed on the Psychiatric Services Online Information System. Results: Four specific pathways of referral and acceptance into an adult mental health service were identified: not referred, referred with immediate engagement, referred with delayed engagement, and referred with no engagement and not accepted. Principal discharge diagnosis, length of stay, and housing situation on discharge were all found to influence likelihood of referral. Only principal discharge diagnosis was found to influence successful acceptance into an adult mental health service. Conclusions: The factors found to influence transition pathways in the present study were largely consistent with findings from the UK. Findings of the present research can assist clinicians to make more informed decisions when discussing transition with clients. More broadly, findings can be used by policy makers to support the formation and maintenance of transition protocols.